Clostridium difficile toxigénico en muestras de heces: nuevo diagnóstico laboratorial - Chamba Lapo, Rubby Karolina (2024)
Clostridium difficile (CD) is a gram-positive, strictly anaerobic, spore-forming bacillus, the main causative agent of infectious diarrhea associated with medical care in adults and the use of antimicrobials. C. difficile infection (CDI) is manifested by both factors. main virulence: toxin A (TcdA) and toxin B (TcdB). CD has a hypervirulent strain NAP1/027 associated with high rates of morbidity and mortality. The diagnosis of this infection is confirmed by laboratory, using direct or indirect methods that have different degrees of efficacy and diagnostic effectiveness. The purpose of this study is to identify the prevalence of CD strain NAP1/027 and the best diagnostic method to identify toxigenic Clostridium difficile in stool samples. To this end, it has been proposed to follow the methodology for systematic reviews based on the search for the problem with the guidelines of the Cochrane system and screening the information following the PRISMA method, evaluating the quality of each document using the JBI tool for precision studies. diagnostic tests ensuring that the trials used for this review comply with the guidelines established for their methodology and development, in order to avoid the highest percentage of risk of bias possible. A total of 12 articles were included for this review in which the average prevalence of the toxigenic Clostridium difficile strain NAP1/027 in stool samples worldwide was found to be 25.23% and the best diagnostic method to identify Clostridium toxigenic difficile in stool samples is the single tube method based on the fluorescence readout of the OC-MAB platform (orthogonal CRISPR system combined with multiple RPA). The growing increase in CD infections constitutes a serious health problem if there is no adequate clinical management